What can a mother die of at the Parakou University Hospital Center in Africa? - Adisso, Sosthene; Agbossaga, Gisele-Estelle T.; Ntakwinja, Mukanire (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Maternal mortality is a scourge that severely undermines Benin and affects its development. The fact is that despite the efforts that have been made for decades, the causes remain unchanged. What is the evolution of maternal deaths in the maternity CHUD of the Borgou-Alibori which serves the departments of the Borgou and the Alibori populated by 1,245,264 inhabitants? The objectives of the present study aim to assess the ratio of maternal deaths, profile of deceased women, causes of death. Methods: This study took place at the maternity CHUD-B and covered a five-year period from January 1, 2010 to December 31, 2014. This is a retrospective, cross-sectional, analytical and descriptive study covering 113 cases of maternal death. Results: During this period, we noted from 2010 to 2014 an evolution from 953 to 1388 deaths for 100,000 live births. The deceased women were for the most part illiterate, without any profession and married. The main direct causes of maternal deaths in order of frequency are hemorrhage 47.7%, eclampsia 19.5%, infection 9.8%, dystocia 3.5%. Indirect causes account for 19.5% of maternal deaths. The administration of emergency obstetric care has occurred under conditions where the third delay is found in 22.1% of cases with as the dominant factor the non-availability of blood products. Conclusions: In the face of these circumstances, it is necessary to revise the system of the management of the Gravido-puerperium in the peripheral formations and in the maternity of the CHUD-B and then the conditions of transfer in order to positively influence the reduction of the mortality Maternal.